Conquer Fear of Heights Using Virtual Reality Exposure Therapy With Cognitive Restructuring - Faizah, Miftah; Ramdhani, Neila; Utami, Muhana Sofiati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2024)
Acrophobia has traditionally been treated using exposure therapy; however, virtual reality technology has emerged as an alternative that minimizing security risks by presenting three-dimensional stimuli. This study aimed to investigate virtual reality exposure therapy-cognitive restructuring (VRET-CR) effectiveness in reducing acrophobia symptoms. In a pretest-posttest control group design, 27 participants were randomly assigned to the experimental group (n=13) and the control group (n=14). An independent sample t-test revealed a significant differences in the gain scores of the acrophobia questionnaire (AQ) 1 [t (17.08) = -6.173; p <0.05] and AQ 2 [t (25) = -4.250; p <0.05] between these groups. Scores on the State-Trait Anxiety Inventory (STAI) and Autonomic Perception Questionnaire (APQ) decreased after six exposure sessions, supporting these findings. Skin conductance and respiratory rate changes during therapy were less significant than heart rate changes. Overall, the results demonstrated the effectiveness of VRET-CR in reducing acrophobia symptoms.